FROM BASEMENT MEMBRANE DEFECTS TO PRECISION MEDICINE: ADVANCES IN ALPORT SYNDROME - Karolina Krowiak; Anita Krowiak; Anita Warzocha; Piotr Pitrus; Karol Bednarz; Maria Jasiewicz; Gabriela Majka; Magdalena Kowalczyk; Wiktoria Hander; Aleksandra Karnas (International Journal of Innovative Technologies in Social Science, 2025)
Alport syndrome is a hereditary disorder characterized by progressive renal dysfunction, sensorineural hearing loss, and ocular abnormalities, resulting from mutations in COL4A3, COL4A4, COL4A5. The clinical phenotype ranges from isolated hematuria to early-onset end-stage renal disease, with variability determined by inheritance patterns and specific genotypes. Diagnosis relies on combination of clinical assessment, renal biopsy with electron microscopy, and targeted genetic testing, enabling precise characterization of disease severity and informing management strategies. Current therapeutic approaches focus on renoprotective interventions, primarily angiotensin-converting enzyme inhibitors and angiotensin receptor blockers, with emerging evidence supporting adjunctive use of sodium-glucose cotransporter 2 inhibitors. Novel experimental therapies, including endothelin receptor antagonists, glucagon-like peptide-1 receptor agonists, microRNA-targeted treatments, and gene or stem cell-based strategies, aim to address underlying molecular mechanism, though long-term safety and efficacy require further investigation. Advances in understanding genotype-phenotype correlations, combined with improvements in diagnostic workflows and therapeutic modalities, provide opportunities to slow disease progression, optimize clinical outcomes, and improve quality of life. This review summarizes current knowledge of AS, emphasizing clinical heterogeneity, diagnostic approaches, and evolving treatment paradigms.